The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1159/000046598
|View full text |Cite
|
Sign up to set email alerts
|

The Picture of Inflammation: A New Concept That Combines the White Blood Cell Count and Erythrocyte Sedimentation Rate into a New Hematologic Diagnostic Modality

Abstract: Background: Physicians who work in small clinics, far away from medical centers, cannot obtain relevant information regarding the acute phase response at low cost and real time. Methods: We adopted a simple slide test and image analysis to determine the number of white blood cells in the peripheral blood, their degree of adhesiveness/aggregation as well as that of the red blood cells. Three independent observers scored the images into categories of no (1), mild (2), moderate (3) or severe (4) inflammation. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 16 publications
3
16
0
Order By: Relevance
“…When there is no aggregation, 100% of the slide area is covered with erythrocytes, while during aggregation this percentage is reduced owing to the appearance of clear areas between the groups of aggregated cells. The coefficient of variations of this methodology was depicted elsewhere [21][22][23].…”
Section: The Erythrosense Technologymentioning
confidence: 99%
“…When there is no aggregation, 100% of the slide area is covered with erythrocytes, while during aggregation this percentage is reduced owing to the appearance of clear areas between the groups of aggregated cells. The coefficient of variations of this methodology was depicted elsewhere [21][22][23].…”
Section: The Erythrosense Technologymentioning
confidence: 99%
“…This means that if a person presents with 2.7% of the WBC in clusters of four or more cells, we could assume with 94% certainty that a bacterial infection is present. Also noteworthy is that the size distribution of clusters revealed that there are larger aggregates in the bacterial group compared to the viral and control groups, and this applied both for capillary and venous blood.The image analyzer is a simple, cheap and rapid tool to screen for the presence of relatively large leukocyte aggregates suggestive for the presence of a bacterial infection [43]. Based on the previous observations [14,26,[39][40][41][42], we do suggest that the determination of the size distribution of aggregated leukocytes be taken into consideration during the workup of a patient with an acute febrile condition and when the differentiation between viral and bacterial infection is relevant.…”
Section: Discussionmentioning
confidence: 90%
“…The slides were scanned in an automated image analyzer (Inflamet TM ) as previously described [11]. Nine systematically chosen areas each covering 0.6 mm 2 were analyzed by the Inflammation Meter application software in respect to type of cell (based on cell size, shape, and density of the cytoplasma), the distance between neighboring cells, and the percentage of the areas covered by cells.…”
Section: Methodsmentioning
confidence: 99%
“…The aggregation level of a slide was then defined as the percentage of leukocytes in clusters of at least 2 cells. In the same manner, erythrocyte aggregation (or adhesiveness) was assessed as the percentage of the slide not covered by red blood cells (see [11] for details).…”
Section: Methodsmentioning
confidence: 99%